Students’ Error in Writing Simple Past Sentences - Rini Nurul Amla; Faudi Faudi (Universitas Serambi Mekkah, 2022)
The purpose of this study is to find out the types of errors made and difficulties faced by the students at SMA Negeri 1 Ingin Jaya when writing simple past sentences. This study used a descriptive design. The sample was 30 grade-10 students at SMA Negeri 1 Ingin Jaya. The instruments used in this study were tests and interviews that was given to the participants to find out the types of errors and the difficulties faced by them in writing the simple past tense. The data analysis technique used in this study were the percentage formula for test and interview analysis based on Miles et al. (2013). Based on the results of this study, it was found that there were 26% of students made an error in omission, 71,33% in misinformation and 2,67% in misordering. The highest error was in misinformation. Based on the result of the interviews, it was found that there were several difficulties faced by students in writing simple past tense sentences; the students have difficulties in determining and using the correct form of regular and irregular verbs, and they have lack of knowledge about simple past tense material.